PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH PADA DEPOT ISI ULANG AIR MINUM “MATTHEW WATER “ WAILELA RUMAHTIGA KOTA AMBON - Delya Vega Pattiwael; Daniel Yohannis Titapasanea; Nicodemus Rahabeat (Jurnal Administrasi Terapan, 2023)
This research aims to apply Financial Accounting Standards (SAK) for Micro, Small and Medium Enterprises (MSMEs) at the "Matthew Water" Drinking Water Refill Depot - Wailela Rumahtiga Ambon City. SAK EMKM is an accounting standard aimed at meeting the financial reporting needs of micro, small and medium entities. The "Matthew Water" drinking water refill depot has not implemented financial reports in accordance with SAK EMKM and considers that the accounting process is not very important to implement.This research uses a qualitative method with a descriptive approach. This research was carried out in four stages, namely, (1) data collection was carried out by interviews and observations, (2) data reduction, (3) data presentation, (4) and drawing conclusions.The results of the research show that the financial records that have been carried out by the "Matthew Water" drinking water refill depot are still very simple, namely limited to recording cash in and cash out, the reason is limited knowledge. Based on the cash incoming and outgoing records obtained from the business owner, SAK EMKM is applied in preparing financial reports. The implementation of SAK EMKM includes three components, namely the financial position report with total assets of IDR 106,482,000 and total equity and liabilities of IDR 106,482,000. The Profit and Loss Report shows Profit of IDR 7,964,750 and Notes to the financial statements.